Septage management related regulatory and institutional aspects and needs in Sri Lanka. A review - Fernando, Sudarshana; Drechsel, Pay; Manthrithilake, Herath; Jayawardena, Lalith (2014)
Urbanization, population growth and rapid development have created a notable shift in septage* management in Sri Lanka, necessitating a vast and rapid improvement in the service of mechanized septage collection by trucks and finding additional space to meet the increasing septage disposal needs. According to data collected in 2012, 58% of the Local Authorities (LAs) in Sri Lanka have access to septic truck services. Septage (from septic trucks) appears as a non-traditional and fairly new urban waste stream without proper regulatory and institutional arrangement to manage. This paper contains a comprehensive legal, regulatory and institutional analysis of the present situation, and identify the needs and gaps that need to be filled to establish a sustainable septage management service in Sri Lanka. This review has elicited the need for a new array of regulatory and institutional interventions from national level to local level to manage septage.